Religion and Mental Health: A Critical Reflection in Consequence of Four Reviews (1969-2013) - Peter J., Verhagen (International Journal of Psychotherapy Practice and Research, 2017)
Religion and spirituality correlate positively with mental health. Although it is true generally spoken, it is too simplistic. On the basis of four reviews, from the period 1969-2013, the progress that was made and the achievements that were accomplished will be shown. In doing their empirical work the researchers managed to fit in with the evidence-based medicine approach. Thus, their work corresponded more and more to the standard scientific requirements. However, what are the consequences of that fit? And, in what sense could religion become part of ‘the most effective means of achieving health’? That asks for a critical ethical evaluation. Utilitarianism turns out to be the ethical basis of evidence-based medicine and achieving health is its central value. As a consequence, compared with religious traditions religion gets a different content with a strong experiential-expressive focus. That focus fits perfectly with modern Western values. Finally, the findings and discussions will enable us to plot four preliminary scenarios for the impact of research on religion and spirituality on psychiatry and mental health.
Keywords: religion; spirituality; mental health; values; evidence-based medicine; ethics; scenarios